Anthropogenic habitat loss accelerates the range expansion of a global invader. (15th June 2021) - Wang, Xuyu; Yi, Tao; Li, Wenhao; Xu, Chunxia; Wang, Supen; Wang, Yanping; Li, Yiming; Liu, Xuan
Abstract: Aim: Understanding the patterns and correlates of the range expansion of established alien species is crucial for predicting invasion impacts and developing effective control strategies. With accelerating globalization, it is key to identify the interactions of different global change processes, such as how land‐use change may influence range expansion, yet empirical studies remain limited. Location: Liuji Town, Jiangsu Province, China. Methods: We first divided the study area into 128 grids with a resolution of 1 × 1 km and conducted visual encounter surveys over two years for a total of 492 water bodies to explore the establishment and range expansions of a global notorious invader, the American bullfrog Lithobates catesbeianus (Shaw, 1802) (= Rana catesbeiana (Shaw, 1802)) using generalized linear mixed models. Then, we investigated the residence time of the established bullfrogs in each water body based on a questionnaire survey. We quantified the habitat loss and range expansion of the past 30 years via GIS‐based spatial analysis and explored their temporal dynamics using the breakpoint regression technique. Results: We found that the area of suitable habitats was the most important variable positively related to the bullfrog establishment. There was a similar temporal trend of the range expansion and habitat loss, although the optimal time of habitat loss was slightly earlier than that of the great increase in bullfrog range expansion. Overall, the bullfrogs tended to expand faster with greater habitat loss after controlling for temporal non‐independence. Main conclusions: Our results demonstrated that loss of suitable habitats may facilitate invaders with faster range expansion to occupy the remaining limited resources. Alien species might thus accelerate invasions under human‐induced land‐use modifications in the era of global change. The time lag between range expansion and habitat loss is the golden window for preventing the spread of established alien species in disturbed habitats.